Social capital and cannabis supply - Scott, J.; Grigg, J.; Barratt, Monica; Lenton, Simon (Sage Publications, 2017)
© 2017, © The Author(s) 2017. The distribution of cannabis in Australia is examined with reference to motivations for supplying drugs. We argue that the distribution of cannabis in Australia is best understood with reference to the concept of social supply, where a supplier, not considered to be a ‘drug dealer proper’, brokers, facilitates or sells drugs, for little or no financial gain to friends and acquaintances. The article draws on data from surveys and interviews with 200 young Australian cannabis users, almost all of whom had also supplied cannabis at some point in their lifetime. We further theorise the concept of social supply with reference to social capital. We argue that a sociological understanding of drug distribution should focus on drug communities, as opposed to markets, describing the features of social organisation that exist between people within social networks and related implications that such features might have in terms of social harm and well-being.